Synthesis and Characterization of Some New 1,3Oxazepine Derivatives - Saoud, S. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
In this study, Schiff’s bases [S3,S4] were synthezied by condensation of N,N-dimethyl amino benzaldehyde with primary aromatic amine[N-(hydrazinyl methyl)benzamide]. These Sciff’s bases were found to react with maleic anhydride and phthalic anhydride to give 1,3Oxazepine[S5,S6,S7,S8] in good yields. The structures confired by m.p ,T.L.C.,FT.IR and 1H-NMR (of some of them).